"Centro regional multipropósito ""Cerma"", Propuesta de revitalización urbana y escenarios dotacionales como mecanismo para el desarrollo y la equidad social en el municipio de Apulo, Cundinamarca" (2018)
"The municipality of Apulo, is located in the Province of Tequendama, Department of Cundinamarca, at an approximate distance of 101 km from Bogotá, on the road that leads to Girardot (way La Mesa), being an important corridor for the country, its Climate, environmental conditions and its high tourist-regional level. Historically the municipality has had a period of consolidation and a period of decline between the years 1888 - 1978 and 1979 - 2018 respectively. Events such as the fire of the hotel ""Juntas de Apulo"" in 1952, or the last trip of the train in the municipality in 1978 will mark the end of its period of growth and development for a time of urban decadence that prevails today (plan of development municipality of Apulo 2016-2019), what is also evident in the lack of equipment, the quality of public space, migrations and abandoned buildings among other problems. In the search for integral development, it is necessary to promote from the architecture alternatives for urban and environmental improvement, the consolidation of the population and the creation of new social, economic, and economic opportunities for the municipality of Apulo from the revitalization; Affirms kevin Lynch in his writing Image of the city (1959), which is ""The majority of observers group their elements in integrated organizations"", that is, the city is experienced as a whole whose parts depend on each other and which are relatively fixed in relation to one another. For this reason, the present project corresponds to 4 dimensions (urban-environmental, architectural, heritage and social), to counteract urban deterioration, emphasized in a urban intervention and the creation of a multipurpose architectural space that provides a solution to the problems mentioned previously and the social dynamics that this territory presents"